Glucocorticoid susceptibility and in vivo ABCB1 activity differ in murine B cell subsets - KELLI M. DA COSTA; RAPHAEL C. VALENTE; JOYLE M.C. DA SILVA; LUCIANA S. DE PAIVA; VIVIAN M. RUMJANEK (Anais da Academia Brasileira de Ciências)
Abstract Glucocorticoids are produced and released by the adrenal gland and become elevated in response to stress. Although glucocorticoids are well known for their immunosuppressive effects, less is known about their effects on B cells. ABCB1 is an efflux pump expressed in both cancer and normal cells, modulating the gradient of various metabolites, including hydrocortisone. Our goal was to evaluate the effect of this glucocorticoid on murine B cell differentiation and whether sensitivity to hydrocortisone could be related to ABCB1 activity in vivo. C57BL/6 mice received one or three consecutive i.p. injections of hydrocortisone (70, 140 and 200 mg/kg/day). ABCB1 activity was evaluated via the rhodamine-123 transport and inhibited by cyclosporin A in hydrocortisone-treated and control mice. Cells from bone marrow, spleen and blood were counted, incubated with antibodies and analyzed by flow cytometry. A single hydrocortisone injection did not alter the number of bone marrow subsets. Conversely, three daily injections were able to reduce the cell number of most bone marrow subsets, excepting c-kit-sca-1+ and mature B cells. This treatment reduced marginal zone, follicular and transitional B cells, though splenic subsets were more resistant than bone marrow B cells. Recirculating follicular B cells in the blood were resistant to hydrocortisone. With the exception of follicular B cells, all subpopulations exhibited ABCB1 activity. However, hydrocortisone treatment did not affect ABCB1 activity in most subsets analyzed. Results suggest that hydrocortisone is able to regulate B cell lymphopoiesis although ABCB1 activity is not related to the susceptibility to that glucocorticoid in B cell subsets.